2004
DOI: 10.1161/01.cir.0000124720.18538.dd
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Improves Endothelial Dysfunction in Systemic Vasculitis

Abstract: Background-Endothelial vasomotor dysfunction and markers of systemic inflammation are independent determinants of cardiovascular risk. However, the link between clinical inflammation and endothelial dysfunction is unclear. The aim of this study was to use anti-neutrophil cytoplasmic antibody-associated systemic vasculitis (AASV) as a model of systemic inflammation in which to test the hypothesis that inflammation is associated with endothelial dysfunction and can be reversed with anti-tumor necrosis factor-␣ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(56 citation statements)
references
References 40 publications
4
49
1
2
Order By: Relevance
“…Raza et al assessed endothelial function by measuring flow-mediated brachial artery vasodilatation after reactive hyperaemia [53] and found significantly impaired vasodilatation in patients with active vasculitis that normalized during therapy. Endothelial function as assessed by plethysmography after infusion of acetylcholine demonstrated impaired responses [54]. However, contradictory results were found in two other studies [55,56] where increased vasodilator responses after acetylcholine infusion were observed.…”
Section: Occurrence Of Accelerated Atherosclerosis In Vasculitismentioning
confidence: 85%
“…Raza et al assessed endothelial function by measuring flow-mediated brachial artery vasodilatation after reactive hyperaemia [53] and found significantly impaired vasodilatation in patients with active vasculitis that normalized during therapy. Endothelial function as assessed by plethysmography after infusion of acetylcholine demonstrated impaired responses [54]. However, contradictory results were found in two other studies [55,56] where increased vasodilator responses after acetylcholine infusion were observed.…”
Section: Occurrence Of Accelerated Atherosclerosis In Vasculitismentioning
confidence: 85%
“…By implication, long-term suppression of the systemic inflammatory response should reduce the risk of CHD. Results of early epidemiologic studies of methotrexate therapy are commensurate with this hypothesis (4), as is evidence suggesting that suppression of inflammation improves endothelial-dependent function (5,6).…”
mentioning
confidence: 84%
“…Thus far, no adequately placebocontrolled study examining the effect of TNF modulation on a range of established and novel vascular risk factors has been reported. Currently available information from small, often uncontrolled studies suggests that TNF blockade either increases (7) or decreases (8) the level of high-density lipoprotein (HDL) cholesterol, with more consistent effects on endothelial-dependent vascular function (5,6).…”
mentioning
confidence: 99%
“…Additionally, TNF-α deficient mice were not affected by the galactosyl ceramide [40]. Recent studies have shown that anti-TNF-α therapy could significantly improve endothelial functions in human subjects with vascular inflammation [41,42]. However, it is not know whether this therapy could be correlated with ceramide production in these individuals.…”
Section: Tumor Necrosis Factor-α and Ceramidementioning
confidence: 99%